The Inclusion of the Lived Experience of Disability in Policymaking - Laufey Löve; Rannveig Traustadóttir; Gerard Quinn; James Rice (Laws, 2017)
This paper examines the process under way in Iceland to align national law with the UN Convention on the Rights of Persons with Disabilities, focusing on the Convention’s call for the active involvement of disabled people and their representative organizations in policy and decision making on matters that affect them. The paper draws on comments submitted by Icelandic DPOs on draft legislation intended to replace the existing law on services for disabled people, focusing on comments relating to their ability to participate in and affect the policymaking process. Furthermore, it draws on interviews with leaders of representative organizations of disabled people that solicited their views on the issue. The findings indicate that there is a reluctance on behalf of Icelandic authorities to make changes to the established process, which limits the active participation of disabled people and their representative organizations. The draft legislation has neither been revised to include provisions for expanding the participation of DPOs in policy and decision making, nor to ensure that disabled people themselves participate in the process.